Development of functional anti‐Gn nanobodies specific for SFTSV based on next‐generation sequencing and proteomics. (26th October 2022) - Wang, Binghao; Huang, Bilian; Li, Xinyu; Guo, Yan; Qi, Guantong; Ding, Yibing; Gao, Haidong; Zhang, Jingzi; Wu, Xilin; Fang, Lei
Abstract: Severe fever with thrombocytopenia syndrome (SFTS) is an acute infectious disease caused by novel bunyavirus (SFTSV), with a mortality rate of 6.3% 30%. To date, there is no specific treatment for SFTS. Previously, we demonstrated that SFTSV surface glycoprotein (Glycoprotein N, Gn) was a potential target for the development of SFTS vaccine or therapeutic antibodies, and anti‐Gn neutralizing antibodies played a protective role in SFTS infection. Compared with traditional antibodies, nanobodies from camelids have various advantages, including small molecular weight, high affinity, low immunogenicity, convenient production by gene engineering, etc . In this study, we combined next‐generation sequencing (NGS) with proteomics technology based on affinity purification‐mass spectrometry (AP‐MS) and bioinformatics analysis to high‐throughput screen monoclonal anti‐Gn nanobodies from camel immunized with Gn protein. We identified 19 anti‐Gn monoclonal nanobody sequences, of which six sequences were selected for recombinant protein expression and purification. Among these six anti‐Gn nanobodies, nanobody 57, 493 was validated to be highly specific for Gn. The innovative high‐throughput technical route developed in this study could also be expanded to the production of nanobodies specific for other viruses like SARS‐CoV‐2.